Development of Android-based application on volume material in grade V - Olisna, Olisna; Julia, Julia; Iswara, Prana Dwija; Ismail, Ali; Gusrayani, Diah; Isrokatun, Isrokatun (Jurnal Pendidikan Matematika RAFA, 2023)
In learning mathematics, especially volume material, students still have difficulty understanding the concept. One of the causes is the lack of use of learning media in the classroom to make it easier for students to understand the lesson. This study aims to develop learning media in the form of android-based applications about volume in class V and to determine the feasibility of the applications that have been developed. The research method used in this research is Research and Development (R&D) with the ADDIE development model. The data collection technique used in this study was an expert validation questionnaire and a user response questionnaire. The results showed that the developed application received a material and language expert validation score of 93.91%, and a media expert validation score of 86.67%. In addition, the results of product trials in small groups received a score of 98.33%, and the test results from the large group trial were 96.48%. This android application media on volume material is very feasible to use in learning.